Participating in non-formal learning: patterns of inequality in EU-15 and the new EU-8 member countries - Roosmaa, Eve-Liis [Verfasser]; Saar, Ellu [Verfasser] (My University, 2010)
"We concentrate on the following research questions: (1) Do the structure of the educational system and its interaction with the labour market affect the training gap between low-skilled blue collar workers and high-skilled white collar workers? and (2) Do the ways that institutional systems shape opportunities for lifelong learning differ between EU-8 and EU-15 member countries? We used aggregate and national data on participation in non-formal learning from European Union countries, based on an ad-hoc module included in the European Union Labour Force Survey (EU-LFS) 2003. Analysis indicated that, as suggested by theory, institutional factors are significant for EU-15 member countries. The predictive power of these factors for EU-8 member countries is rather low and varies significantly by countries." (Autorenreferat, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; L 2.1.1 Informelles Lernen; S 1.5.2 Berufliche Weiterbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.2 Europa; Lebenslanges Lernen; Informelles Lernen; Berufliche Weiterbildung; Weiterbildungsbeteiligung; Bildungschancengleichheit; Einflussfaktor; Interkulturelle Faktoren; Bildungsabschluss; Europäische Union